Regulation of Nuclear Factor κB (NF-κB) Transcriptional Activity via p65 Acetylation by the Chaperonin Containing TCP1 (CCT) - Pejanovic, Nadja (2012)
The NF-κB family member p65 is central to inflammation and immunity. The purpose of this study was to identify and characterize evolutionary conserved genes modulating p65 transcriptional activity. Using an RNAi screening approach, we identified chaperonin containing TCP1 subunit η (CCTη) as a regulator of Drosophila NF-κB proteins, Dorsal and Dorsal-related immunity factor (Dif). CCTη was also found to regulate NF-κB-driven transcription in mammalian cells, acting in a promoter-specific context, downstream of IκB kinase (IKK). CCTη knockdown repressed IκBα and CXCL2/MIP2 transcription during the early phase of NF-κB activation while impairing the termination of CCL5/RANTES and CXCL10/IP10 transcription. The latter effect was associated with increased DNA binding and reduced p65 acetylation, presumably by altering the activity of histone acetyltransferase CREB-binding protein (CBP). We identified p65 lysines (K) 122 and 123 as target residues mediating the CCTη-driven termination of NF-κB-dependent transcription. We propose that CCTη regulates NF-κB activity in a manner that resolves inflammation.